Análisis de la desgravación arancelaria por efectos del TLC Colombia-EE.UU (2018)
The implementation of neoliberal models, involve further reducing barriers to trade, under the neoliberal model, the commercial opening is key element for the development and growth of nations. Reason why Colombia in recent years has led to the signing of several trade agreements with the aim of deepening trade relations and get in this way unilateral access to certain markets, like that of the United States, a nation of great importance for the Colombian economy, since it is the main trading partner of Colombia and one of the largest and most important markets in the world. The Colombia-US FTA has an impact on public finances, product of the tariff reduction process, since, it affects the behavior of the collection of the tributary income of the central sector of the Nation. This research seeks to perform a disaggregated analysis of the main effects in monetary terms.